Credit Risk Measurement Under Basel II : An Overview and Implementation Issues for Developing Countries - Stephanou, Constantinos; Mendoza, Juan Carlos (World Bank, Washington, DC, 2012)
The objective of this paper is to provide an overview of the changes in the calculation of minimum regulatory capital requirements for credit risk that have been drafted by the Basel Committee on Banking Supervision (Basel II). Even though the revised credit capital rules represent a dramatic change compared to Basel I, it is shown that Basel II merely seeks to codify (albeit incompletely) existing good practices in bank risk measurement. However, its effective implementation in many developing countries is hindered by fundamental weaknesses in financial infrastructure that will need to be addressed as a priority.